Envolver o que nos envolve : permacultura e sítios ecológicos em paisagens multiespécies na Serra do Espinhaço. - Gabrielly Merlo de Souza (2020)
In the face of contemporary environmental challenges, human-centered epistemologies have been depleted; on this basis, researches that aim to overcome anthropocentric and constructivist approaches, in favor of relational and compositional perspectives and ontologies, have gained space in the humanities (Viveiros de Castro, 2012; Tsing, 2015; Haraway, 2016). In the midst of this discussion, the social lives of other species emerge as a fruitful and challenging field of study for the humanities, which has been called by some authors as a “multispecies turn” (Kirksey & Helmreich, 2010). In this research, I was guided by this discussion to tell my ethnographic and agroecological experience in the permacultural sites existing in the region of Serra do Cipó and Serra do Espinhaço, in Minas Gerais. Permaculturists' personal knowledge, as well as practices and trajectories, have guided me to weave a narrative that offers vivid stories of multispecies encounters and possible ecological futures – a task I accomplished reading the way these characters devote time to care, but also walking and observing local / global, natural / social landscapes, that intertwine non-generic environmental perspectives. My interest in this study was to speculate on new investigative possibilities involving contemporary ecological thinking and new meanings of environmental ethics (“terrana*”).